Towards an Integrative Taxonomy of Social-Emotional Competences - Schoon, Ingrid (Frontiers in Psychology, 2021)
Social-emotional competences are critical for positive development and significantly predict educational and occupational attainment, health and wellbeing. There is however a lack of consensus about the number of core competences, and how these are defined and operationalised. This divergence in approach challenges future research as well as the scientific usefulness of the construct. In an effort to create an integrative framework, this focused review evaluates different approaches of conceptualizing and assessing social-emotional competences. Building on shared conceptions, an integrative taxonomy “DOMASEC” is introduced, specifying core domains and manifestations of social-emotional competences that bridge across frameworks focusing on social and emotional learning, personality traits (such as the Big Five) and self-determination theory. Core domains include intrapersonal, interpersonal and task-oriented competencies, differentiating between affective, cognitive and behavioral manifestations of competences across these domains. It is argued that the integrative taxonomy facilitates the conceptual specification of key constructs, that it helps to better organise the multitude of terms and definitions used, and to guide the conceptualisation and operationalisation of social-emotional competences and their various facets.